New methodology shows that 258 million children, adolescents and youth are out of school (UNESCO, 2019)
Three years after the adoption of Sustainable Development Goal 4 (SDG 4) and the promise to provide universal primary and secondary education, there has been no progress in reducing the global number of out-of-school children, adolescents and youth. This fact sheet by the UNESCO Institute for Statistics (UIS) highlights the most recent statistics on trends at the global and regional levels, based on a revised calculation method that provides more precise estimates of the out-of-school population.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; approches et analyses; discipline; femmes*; inégalités; périodes historiques; systèmes d'oppressions; éducation